BAWASLU DAN PENEGAKAN HUKUM PEMILU - Munandar Nugraha Nugraha (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2020)
Election law enforcement is a necessity in an election that is democratic and has legal provisions. Election law enforcement agencies are the key to the implementation of democratic and fair elections. No matter how small the violations that occur, it is important to follow up, so that substantial democracy can be achieved and carried out. The reconceptualization of institutions authorized to enforce election law is important to be formulated in the revision of the Election Law. Activists and stakeholders who are concerned about electoral studies are obliged to provide contributions, ideas for the realization of elections and electoral justice in subsequent elections.